Can society be commodities all the way down? Post-Polanyian reflections on capitalist crisis - Fraser, Nancy (Economy and Society, 2014)
In his classic 1944 book, The great transformation, Karl Polanyi traced the roots of capitalist crisis to efforts to create ‘self-regulating markets’ in land, labour and money. The effect was to turn those three fundamental bases of social life into ‘fictitious commodities’. The inevitable result, Polanyi claimed, was to despoil nature, rupture communities and destroy livelihoods. This diagnosis has strong echoes in the twenty-first century: witness the burgeoning markets in carbon emissions and biotechnology; in child-care, schooling and the care of the old; and in financial derivatives. In this situation, Polanyi's idea of fictitious commodification affords a promising basis for an integrated structural analysis that connects three dimensions of the present crisis: the ecological, the social and the financial. This paper explores the strengths and weaknesses of Polanyi's idea.
Keywords: capitalist crisis; commodification; domination; double movement; fictitious commodities

The politics of Piketty: what political science can learn from, and contribute to, the debate on Capital in the Twenty-First Century - Hopkin, Jonathan (The British Journal of Sociology, 2014)
Thomas Piketty's imposing volume has brought serious economics firmly into the mainstream of public debate on inequality, yet political science has been mostly absent from this debate. This article argues that political science has an essential contribution to make to this debate, and that Piketty's important and powerful book lacks a clear political theory. It develops this argument by first assessing and critiquing the changing nature of political science and its account of contemporary capitalism, and then suggesting how Piketty's thesis can be complemented, extended and challenged by focusing on the ways in which politics and collective action shape the economy and the distribution of income and wealth. Although Capital's principal message is that ‘capital is back’ and that without political interventions active political interventions will continue to grow, a political economy perspective would suggest another rather more fundamental critique: the very economic forces Piketty describes are embedded in institutional arrangements which can only be properly understood as political phenomena. In a sense capital itself – the central concept of the book – is almost meaningless without proper consideration of its political foundations. Even if the fact of capital accumulation may respond to an economic logic, the process is embedded in a very political logic. The examples of housing policy and the regulation, and failure to regulate, financial markets are used to illustrate these points.
Keywords: capital; inequality; institutions; political science

Environmental protection as market pathology?: carbon trading and the dialectics of the 'double movement' - Carton, Wim (Environment & Planning D: Society & Space, 2014)
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.
Keywords: EU Emissions Trading Scheme; carbon offsetting; climate change; countermovement; emissions trading; environmental protection; pathology; socioeconomics

Towards a Polanyian Sociology - Gemici, Kurtuluş (European Journal of Sociology, 2014)
Keywords: BLOCK, Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; anthropology; nonfiction; review

Capital in the Twenty-First Century by Thomas Piketty translated by Arthur Goldhammer (Cambridge, MA, Harvard University Press, 2014) - Milkman, Ruth (European Journal of Sociology / Archives Européennes de Sociologie, 2014)
KM - A book review of Capital in the Twenty-First Century that points out the glaring omission of Polanyi.
Keywords: Great Transformation, The (Book); PIKETTY, Thomas; book review

Polanyian Reading of the Socio-Economic Transformations of the European Union - Savevska, Maja (Journal of Contemporary European Studies, 2014)
In an attempt to analyse the socio-economic transformations of the European Union, an increasing number of scholars have resorted to Polanyi's double movement thesis. In doing so, some scholars, by looking at the evidence of intensified marketisation of social relations, consider the EU disembedded; whereas others identify a re-embedding tendency in the recent surge of socio-environmental protection. The paper follows Lacher, Burawoy, Dale and Streeck's readings of Polanyi and argues that the exiting socio-environmental provisions do not re-embed the economy. Socio-environmental protection does not eclipse the neoliberal accumulation strategy which continues to propagate the disembedding tendency, because it fails to decommodify fictitious commodities. The EU is characterised by a heightened intensification of both disembedding and protective tendencies, which Polanyi contends is disruptive in nature. What emerges out of the dialectics between neoliberalisation and socio-environmental provisions is a decelerated rate of change, which, although it temporarily secures the habitation of man, prevents the inception of a synthesis that is capable of sublating the contradictions of the marketisation/protection binary. Moreover, we have a paradoxical situation wherein the socio-environmental measures, despite their protective invocation, are predicated on deepened commodification.
Keywords: European Union; commodification; disembedded; double movement; international political economy; neoliberalism; socioeconomics

Polanyian Themes: From Budapest to the Caribbean - Block, Fred (Development & Change, 2014)
KM: Book review of "From the Great Transformation to the Great Financialization"
Keywords: FROM the Great Transformation to the Great Financialization (Book); From the Great Transformation to the Great Financialization (Book); LEVITT, Kari, 1923-; POLANYI LEVITT, Kari; economic development; nonfiction

Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Keywords: COMMONS, J.R.; COMMONS, John; Great Transformation, The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money

The Precariat - Standing, Guy (Contexts: Understanding People in Their Social Worlds, 2014)
Economist Guy Standing explains how millions of people are in the precariat, and in defining this emerging class, points to the dangerous political and social consequences as well as the exciting progressive revival that this class could produce.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; class inequality; economics; labor; labour; politics; precariat; precarity; social classes; welfare economics

Socioéconomie et démocratie – l'actualité de Karl Polanyi Isabelle Hillenkamp & Jean-Louis Laville (éd.) - Maucourant, Jérôme (Revue de philosophie économique, 2014)
A book review in a French journal
Keywords: book review; economic philosophy

The Anthropology of Money and Finance: Between Ethnography and World History - Hart, Keith; Ortiz, Horacio (Annual Review of Anthropology, 2014)
We review here recent developments in the anthropology of money and finance, listing its achievements, shortcomings, and prospects, while referring back to the discipline's founders a century ago. We take our departure from the work of Marcel Mauss and Karl Polanyi, both of whom combined openness to ethnographic research with a vision of world history as a whole. Since the 1960s, anthropologists have tended to restrict themselves to niche fields and marginal debates. The anthropological study of money and ethnographies of finance, in particular, have been the focus of much research since the 1980s. Despite taking on new objects and directions, anthropologists still find it difficult to connect their situated analyses with global processes and world history. We propose some conceptual and empirical directions for research that would seek to overcome these limitations by integrating ethnography more closely with human history, while stressing the importance of money in shaping world society and attempts to reform it.
Keywords: MAUSS, Marcel, 1872-1950; distribution; economic anthropology; ethnology; exchange; finance; globalization; history; money; politics; world society

A Missed Opportunity - Kesting, Stefan; Hughes, Peter (Erwägen Wissen Ethik, 2014)
The authors respond to arguments raised by political scientist Hartmut Elsenhans in his article "Capitalism and Global History: Some Thoughts on History and Theory," published within the issue. Topics discussed include the double movement theory of political economist Karl Polanyi, social factors that influence capitalism, and the way Elsenhans interpreted modern capitalism using Marxian materialism concepts.
Keywords: ELSENHANS, Hartmut; capitalism; history; materialism

Income Inequality in Advanced Capitalism: How Protective Institutions can Promote Egalitarian Societies - Kollmeyer, Christopher (Comparative Sociology, 2014)
This study develops a Polanyian perspective on income inequality in advanced capitalist countries. Polanyi's historical account of the rise and fall of classic liberalism in Britain illustrated how social groups and society at large devised "protective institutions" to shield themselves from socially destructive market forces. Recent qualitative applications of this idea identify three protective institutions as being the most important - the public sector economy, trade unions, and the family. Using data from 16 Western countries from 1970 to 2010, this study demonstrates that cross-national and temporal variations in these protective institutions explain a considerable amount of the observed patterns of income inequality among these countries, helping to explain why some countries have recently experienced rising inequality but others have not. The study ends by arguing that a Polanyian perspective provides more analytical and theoretical leverage than other sociological approaches to understanding income inequality.
Keywords: The Great U-Turn; capitalism; economic sociology; income distribution; income inequality; labor unions; labour unions; liberalism; protective institutions; research; social groups - research

On the Dialectics of Global Governance in the Twenty-first Century: A Polanyian Double Movement? - Patomäki, Heikki (Globalizations, 2014)
Following decades of economic globalisation and market-oriented reforms across the world, Karl Polanyi'sdouble movementhas been invoked not only to explain what is happening but also to give reasons for being hopeful about a different future. Some have suggested a pendulum model of history: a swing from markets to society leading, in the next phase, to a swing from society to markets, and so on. The double movement can also be understood dialectically as a description of an irreversible historical development following its own inner laws or schemes of development. Going beyond a thesis–antithesis–synthesis pattern, I maintain that conceptions and schemes drawn from dialectics, and especiallydialectical critical realism, can provide better geo-historical hypotheses for explaining past changes and for building scenarios about possible future changes. I analyse political economy contradictions and tendencies, and focus on normative rationality, to assess substantial claims about rational tendential directionality of world history. I argue that democratic global Keynesianism would enable processes of decommodification and new syntheses concerning the market/social nexus. A learning process towards qualitatively higher levels of reflexivity can help develop global transformative agency. Existing contradictions can be resolved by means of rational collective actions and building more adequate common institutions. These collective actions are likely to involve new forms of political agency such as world political parties. (English)
Keywords: 21st century; Keynesian economics; contradiction; critical realism; dialectic; double movement; economics - history; global governance; globalization; market; political economy; political parties; scenario; utopia

Class Struggle or Embedded Markets? Marx, Polanyi and the Meanings and Possibilities of Social Transformation - Selwyn, Benjamin; Miyamura, Satoshi (New Political Economy, 2014)
Marx and Polanyi both held that socialism, in one form or another, was a preferable and possible alternative to capitalism. Their ideas are seen to offer theoretical tools to understand the tensions and contradictions of capitalism, and to inform ways to overcome them. This paper discusses Polanyi's work from a Marxist perspective in order to illuminate his strengths and weaknesses. Its main focus is to discuss Polanyi's juxtaposing of commodification against exploitation, in diagnosing the problems of capitalist expansion. We suggest that by juxtaposing these two moments, Polanyi not only misses out on a crucial arena of capitalist activity (exploitation), but also undermines his own explication of processes of commodification. This has deleterious consequences for his understanding of the prevalence of poverty under capitalism. It also means that his vision of social transformation and of socialism is profoundly different, and potentially antithetical, to that of Marx. We suggest that for Polanyi's conception of de-commodification to gain greater traction it needs to be combined with Marx's analysis of exploitation and class struggle.
Keywords: MARX, Karl, 1818-1883; Polanyi; commodification; exploitation; historical materialism; institutionalism

Informalizing the Economy: The Return of the Social Question at a Global Level - Breman, Jan; van der Linden, Marcel (Development and Change, 2014)
The classical conceptualization of the working class, of workers’ collective action and, especially, of trade unionism, was implicitly or explicitly based on the Standard Employment Relationship that, for a few decades, has been dominant in North America, Europe, Japan and Australasia. The ‘classical’ model of collective bargaining, which has shaped the world's traditional labour movements, was based on this conceptualization. However, it is now increasingly undermined by the rapid spread of ‘informal’ or ‘precarious’ labour in the global North. It is our contention that the ‘classical’ view of the working class and workers’ collective action is fundamentally biased and takes as a norm or standard what was in fact an historical exception. The real norm or standard in global capitalism is insecurity, informality or precariousness, and the Standard Employment Relationship is an historical phenomenon which had a deep impact in a limited part of the world for a relatively short period of time. If, as we argue, the ‘Rest’ is not now becoming like the ‘West’, but the other way round, then the ‘traditional’ forms of collective action that have developed in the North Atlantic region during the last two centuries are gradually losing much of their impact. New forms of collective action are emerging, though these are often still at an embryonic stage. It is, therefore, high time to rethink the concept of the working class and the ways in which it can further its interests.
Keywords: informalization; precarity

Introduction: The ‘Labour Question’ in Contemporary Capitalism - Chhachhi, Amrita (Development and Change, 2014)
The recent upsurge in workers’ struggles globally has bought labour again to the forefront, despite predictions that the working class was no longer relevant as a force for social transformation. Neoliberal globalization, with the hypermobility of capital, has led to the emergence of new forms of flexible work/labour, the co-existence of old and new working classes, and an extreme rise in inequality, realigning class structures nationally and globally. Financialization has ushered in a new regime of accumulation and there is a deepening crisis of reproduction. Can a Marx plus Polanyi theoretical integration capture contemporary dynamics of capitalist globalization and the role of labour? What do the trajectories of such struggles in the South tell us about the limits and potentialities for a counter-capitalist movement? More crucially, is the route to full social citizenship entitlements still possible via employment (with its further extension universally), or is it to be reached by directly demanding citizenship rights, bypassing labour-based demands? How do recent collective actions express workers’ interests/identities as workers, citizens and consumers? What role is the state playing in responding/mediating/facilitating these struggles? The Introduction delineates some of these contentious issues which frame this Forum Debate. The contributors all offer different perspectives and critical insights on the connections between forms of labour, possibilities for action and organization, the relationship between labour struggles and social citizenship and the role of the state in contemporary capitalism. The conclusion reflects on some of the equally controversial proposed alternatives and argues for going beyond minimalism and for the imperative of radical rethinking to ensure dignified work and full social citizenship entitlements as part of a new social emancipatory political project.
Keywords: MARX, Karl, 1818-1883; capitalism; globalization; labor question; labour question; neoliberalism

Reclaiming Karl Polanyi, Socialist Intellectual - Clark, Timothy David (Studies in Political Economy, 2014)
The crisis of neoliberal globalization has led many scholars back to Karl Polanyi in their search for alternatives to the present malaise. The dominant reading appropriates the concepts of embeddedness and the double movement in support of a system of regulated, welfare-state capitalism. This article contends, however, that the concepts of embeddedness and the double movement point not towards the need to regulate capitalist markets, but towards the radical supersession of capitalism itself.
Keywords: Canada; capitalism; globalization; radical change

Alienated Politics: Labour Insurgency and the Paternalistic State in China - Friedman, Eli (Development and Change, 2014)
Is there a labour movement in China? This contribution argues that China does not have a labour movement, but that contestation between workers, state and capital is best characterized as a form of ‘alienated politics’. Widespread worker resistance is highly effective at the level of the firm because of its ability to inflict losses on capital and disrupt public order. But authoritarian politics in China prevent workers from formulating political demands. Despite the spectacular repressive capacity of the state, the central government has in fact responded to highly localized resistance by passing generally pro-labour legislation over the past decade. The consequence of this is that worker unrest has produced important political shifts at the national level, but these have come about without workers’ direct involvement in the process. In other words, workers are alienated from the political object that they themselves have produced. As a consequence, when the state intervenes in labour politics, it appears to be doing so of its own accord, i.e. paternalistically. This framework helps us to understand how worker unrest in China has become highly antagonistic towards employers and the local state, while maintaining the stability of the system as a whole.
Keywords: China; alienated politics; labor movement; labour movement; paternalistic state

Capital–Labour and State Dynamics in Export Horticulture in North-east Brazil - Selwyn, Ben (Development and Change, 2014)
This article argues for the primacy of class relations and struggles as determinants of developmental processes and outcomes, emphasizing the evolving, dialectical nature of these relations. It does so by providing a case study of export horticulture in North-east Brazil. It documents how the region's rural trade union has been able, through mobilizing its membership base, to achieve significant improvements in their livelihoods, pay and conditions. It also shows how the region's employers have responded to these gains by restructuring the labour force in order to attempt to fragment and weaken it. The article pays particular attention to the gender dynamics of class relations.
Keywords: Brazil; Polanyian approaches; class relations; development

Understanding the Precariat through Labour and Work - Standing, Guy (Development and Change, 2014)
This article sets out a framework for analysing the globalizing labour process, arguing that the old dualisms of ‘capital’ versus ‘labour’ and ‘formal sector’ versus ‘informal sector’ are inadequate and unhelpful. It begins by making conceptual distinctions between work and labour and between labour and labour power, and goes on to identify a globalizing class structure in which a ‘precariat’ is emerging as a potentially transformative new mass class. Denied so-called ‘labour rights’ and social entitlements that went with twentieth century industrial citizenship, the growing precariat needs new systems of regulation, social protection and redistribution. These should be based on work and occupation rather than subordinated labour, will require new forms of collective action and representation, and should seek to redistribute the key assets of twenty-first century tertiary societies, including income security, control of time, financial capital and the commons. INTRO: That should be the starting point in trying to come to terms with what has been happening in the ‘Global Transformation’, the painful construction of a global market system, analogous to Karl Polanyi's Great Transformation (1944), which was about the construction of national market systems. The Global Transformation, in which the globalization era may be seen as the disembedded phase, has yielded global class fragmentation, or a globalizing class structure superimposed on preceding class structures across the world. This contention has raised the hackles of some Marxists adhering to nineteenth century imagery. But understanding twenty‐first century developments is surely easier if we see a more nuanced structure than the old Marxist dualism of capitalist (bourgeoisie) and proletariat.
Keywords: precariat

The Food-Energy-Climate Change Trilemma: Toward a Socio-Economic Analysis - Harvey, Mark (Theory, Culture & Society, 2014)
The food-energy-climate change trilemma refers to the stark alternatives presented by the need to feed a world population growing to nine billion, the attendant risks of land conversion and use for global climate change, and the way these are interconnected with the energy crisis arising from the depletion of oil. Theorizing the interactions between political economies and their related natural environments, in terms of both finitudes of resources and generation of greenhouse gases, presents a major challenge to social sciences. Approaches from classical political economy, transition theory, economic geography, and political ecology, are reviewed before elaborating the neo-Polanyian approach adopted here. The case of Brazil, analysed with an `instituted economic process’ framework, demonstrates how the trilemma is a spatial and historical socio-economic phenomenon, varying significantly in its dynamics in different environmental and resource contexts. The paper concludes by highlighting challenges to developing a social scientific theory in this field.
Keywords: climate change; climatic changes; economic geography; energy consumption; energy shortages; food consumption; food security; instituted economic process; limits to growth; peak oil; political ecology; socioeconomics; sociogenesis

Maintenir l'ordre économique, Maintaining the economic order - Gayon, Vincent; Lemoine, Benjamin (Politix, 2014)
La sociologie des politiques économiques défendue dans cet article prend pour objet le travail permanent de construction, de naturalisation et de maintien de l’ordre économique déployé par une multitude d’acteurs et d’instruments techniques. Il s’agit d’ouvrir des enquêtes sur la façon dont prennent forme les processus de désencastrement et de réencastrement de l’économie vis-à-vis des institutions politiques et sociales. Cette piste est suivie en quatre temps. D’abord en soulignant la portée sociogénétique de l’œuvre de Karl Polanyi et son insistance sur l’émancipation disputée et incertaine des pratiques de production et d’échange à l’égard des tutelles traditionnelles. Puis en montrant comment l’invention de l’économie en tant que sphère d’activité autonome suscite foule de résistances et de « mondes économiques renversés », opposant leurs propres normes aux « lois » supposées de l’économie. La configuration de l’après Seconde Guerre mondiale est revisitée comme un laboratoire exemplaire de réencastrement politico-étatique de l’économie. Le désencastrement néolibéral des marchés financiers à l’échelle internationale recompose ensuite les comptes de la puissance publique et privée. Ces ordres économiques balisent simultanément des zones d’accès et, réciproquement, de non-droit à la discussion publique et politique., ENG: The sociology of economic policies argued in this article investigates the permanent work of construction, naturalization and maintenance of the economic order made by a multitude of actors and technical instruments. It consists in describing how the doctrinal project of economy disembeddedness takes shape, detaching itself from the political and social institutions. This program is developed through four steps. First, by offering a constructivist reading of Karl Polanyi writings and highlighting the author’s insistence on the uncertain and contested process of production and exchanges’ practices emancipation vis-à-vis traditional guardianship. Then, by showing how the invention of the economy as an autonomous sphere of activity raises crowd resistance and « reversed economic worlds » settling their own standards and laws by opposition to the economy « rules » and values. The after World War Two configuration is revisited as an exemplary laboratory of Politics and State re-embeddedness of the economy. Then, neoliberal disembeddedness of global capital markets reshapes accounts of public and private powers. These economic orders simultaneously mark out areas of access to and, conversely, of non-entitlement to public and political discussion.
Keywords: constructivist; embeddedness

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

Communication Policy and the "Double Movement" - Ashley, Seth (Javnost-The Public, 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Keywords: communication policy; double movement; economic research; institutionalism (religion); marketing research; media system structure; protectionism

White Knights from the Gulf: Sovereign Wealth Fund Investment and the Evolution of German Industrial Finance - Haberly, Daniel (Economic Geography, 2014)
The period leading up to and following the global financial crisis has been characterized by rising global financial diversity and multipolarity, a process underscored by the growth of so-called sovereign wealth funds (SWFs). To date there has not been any systematic examination of the interactions between this rising global financial diversity and national economic institutional diversity. Here I apply an institutional 'comparative capitalisms' perspective to the analysis of Gulf Cooperation Council ( GCC) SWF investment in German industry since the onset of the global financial crisis. The evidence demonstrates that a growing number of German industrial firms-particularly the major automotive firms at the heart of German industry-have recruited long-term GCC SWF investment as an adaptive response to the stresses of financial restructuring, most importantly the appearance of hostile takeovers as a feature of the German corporate governance landscape. These patterns lend partial support to 'varieties of capitalism' ( VOC) arguments that institutional complementarity and comparative institutional advantage are likely to produce path dependent trajectories of national institutional evolution. They also lend partial support to critiques of VOC, emphasizing, on the one hand, the importance of the Polanyian 'double movement' of market expansion and containment and, on the other, the transnational foundations of national institutional diversity. I conclude that to fully explain these patterns, both VOC theories of institutional complementarity and comparative advantage, and Polanyian theories of the double movement, must be grounded in a 'generalized Darwinian' analysis of population-level selection dynamics.
Keywords: Germany; Gulf Cooperation Council; Polanyian double movement; capitalism; economic geography; financial globalization; foreign investments; generalized Darwinism; industries; liberalization (finance); sovereign wealth funds; variegated capitalism; varieties of capitalism

Embracing ambiguity - lessons from the study of corporate social responsibility throughout the rise and decline of the modern welfare state - Schneider, Anselm (Business Ethics: A European Review, 2014)
In the work of Karl Polanyi, the negative effects of a self-regulating market economy are described as being limited by societal forces such as the policies of the welfare state. With the decline of the modern welfare state since the late 1970s, social activities of business firms are increasingly regarded as an important complement to or even as a substitute for welfare state policies by a part of the literature. However, and controversially, another stream of argumentation regards these activities as being aimed at advancing the reach of market forces. To fully grasp the ambiguous nature of the social activities of business, in this paper I provide an account of affirmative as well as of critical interpretations of these activities throughout the history of modern capitalism. On this basis, the power of critique to disentangle the diverse motivations that underlie the social engagement of business is highlighted as a condition for facilitating a role of business in society that balances economic and social considerations.
Keywords: POLANYI, Karl, 1886-1964; business ethics; capitalism; public goods; research; social responsibility of business; value creation; welfare state

Law and Politics in Europe's Crisis: On the History of the Impact of an Unfortunate Configuration - Joerges, Christian (Constellations, 2014)
EXCERPT [KM]: Karl Polanyi has experienced a renaissance in recent years.13 We refer to his work in our remarks on the failures of the European project for three interrelated reasons: (1) Polanyi has underlined that modern markets were not generated by some evolutionary process but established by political planning.14 Europe's “internal market project” is the best conceivable confirmation of his thesis. (2) One of the most important insights of his work concerns the “social embeddedness” of markets and the economy.15 These insights are of crucial importance because Europe has on the one hand realized that the functioning of markets requires comprehensive regulatory activities but at the same time tends to disregard the economic, political and cultural variety and dependence of markets. (3) Polanyi can also provide clarity with regard to the growing skepticism about so many firmly held beliefs about the benefits of ever more European integration. EXCERPT 2: Led by the prompting of its highest court, Europe is waving the flag of economic freedoms of Europe's market citizens and is retreating from its commitment to collective labor law – once the institutionalized countermovement to the commodification of labor.1
Keywords: European Union; economic law; fictitious commodities; internal market project; social embeddedness

Polanyi in Brussels or Luxembourg? Social rights and market regulation in European insurance - Mabbett, Deborah (Regulation & Governance, 2014)
The decision of the Court of Justice of the European Union to ban sex discrimination in insurance has shown the potential reach of the principle of non-discrimination. This paper discusses the different positions taken by participants in the policy process leading up to the decision, in order to reveal the potential and limitations of non-discrimination as the basis for market-regulatory social policy. It is shown that the European Commission's initial support for prohibiting insurance discrimination faltered with the realization that the measure would have little efficacy as a distributive social policy. It was left to the Court to assert that non-discrimination rights are constitutive for European markets, regardless of their functional and instrumental limitations. The Court's focus was on the market-integrative potential of rights as sources of norms for the conduct of insurance relationships. It is argued that this form of constitutive regulation is distinct from distributive social policy as it does not require that outcomes are egalitarian, but, rather, that the processes governing market relations should respect fundamental rights.
Keywords: Gender Directive; discrimination; insurance; rights; social regulation

Can productivity be socially embedded? Reflections on some productivity measures of 2000s - Kocer, Ruya Gokhan (International Journal of Productivity & Performance Management, 2014)
Purpose – The purpose of this paper is to give an overview of items that are included in recent productivity programmes in various countries and integrate these items with the ideas of virtuous circuit of productivity and socially embedded productivity. Design/methodology/approach – In depth analysis of an illustrative set of productivity measures. The analysis reveals how each measure/programme could make sense to the industrial relations actors. A new conceptual reformulation of analysed measures and programmes. Findings – Bilateral productivity deals between trade unions and employers are not necessarily good from the perspective of national policy making. For this kind of uncoordinated productivity measures, though may be good for individual enterprises, may increase unemployment by pushing other domestic competitors out of the market or compelling them to lay-off workers in a reactive fashion. By drawing on Polanyi, one may argue that it is possible to strike a good balance between productivity concerns and societal interests by embedding the former into the latter. Research limitations/implications – The purpose is to introduce a new conceptualization, thus the empirical material is meant to be illustrative rather than extensive. Originality/value – By using graphical displays and empirical argumentation two new concepts are introduced: first, virtuous circuit of productivity and second, socially embedded productivity.
Keywords: employees; employers; industrial relations research; labor productivity; labor unions; labour productivity; labour relations; labour unions; productivity; research; social embeddedness; social partners

Living permanent liminality: the recent transition experience in Ireland - Szakolczai, Arpad (Irish Journal of Sociology, 2014)
Modernity, or the combination of market economy, liberal democratic polity and a society driven by technological progress, we are led to believe, is the end-state of history; the glorious condition of a fully enlightened society of free citizens equipped with equal rights at which all traditional societies are bound to arrive, after a period of transition which might involve some temporary difficulties or 'sacrifices'. However, and in contrast to this, modernity rather involves an infinite period of transition, in which the stable elements of social life, representing not just rigid external constraints on individual freedom, but also the condition of possibility of meaningful life, are one by one liquidated. This article argues that the anthropological concept 'liminality' is particularly helpful in understanding the formative aspects of transition experiences, like the Celtic Tiger phenomenon in Ireland. It also helps to move beyond the conventional 'transition to modernity' framework by pointing out that advanced modernity is identical to a permanent state of transitionality.
Keywords: FOUCAULT, Michel, 1926-1984; Ireland; POLANYI, Karl, 1886-1964; capitalism; genealogy; liminality; manners & customs; modern society; modernity; technological innovations & economics; tradition; trickster

Moral versus Commercial Economies: Transylvanian Stories - Velicu, Irina (New Political Science, 2014)
Historically, the production of a market society has depended on the commodification of valuables such as land and labour, which has also meant the disembedding of capital from elements of the “primordial,” such as kinship, spiritual relations, and identities. Today we are still witnessing the invocation of such elements of moral economies as a basis for people's collective mobilization against market pressures. The case study in this article refers to Rosia Montana, a semi-urban village in Transylvania where a Canadian corporation is planning to create the largest cyanide opencast mine in Europe. Through attempts at privatizing and commodifying whole areas of social life, the market logic promoted by the corporation in the last twelve years portrays the mine as the “only alternative” for the development of the region. Rosieni and activists have blocked the project for more than fourteen years by reclaiming other fundamental values related to spirituality, ancestry, land, and nature. They challenge the prevailing violence of the market by problematizing the logic of the commercial economy and by re-evaluating what the corporate project devalues. How does the post-communist context inspire a moral critique of global corporate capitalism and a democratic socialist alternative? In this article Polanyi's argument related to the “fictitious commodities” of the market will be used to support the argument that moral principles inspire forms of resistance against commodification in the former Eastern bloc and may produce future alternative forms of development. If one noticed an increase in social and environmental activism in Romania over the last five years would it also be due to the perseverance of Rosieni and its supporters in challenging not only a corporation and some co-opted/corrupted officials, but an entire dominant discourse of neoliberalism?
Keywords: Canadian corporations; Rosia Montana; Transylvania (Romania); commodification; corporate capitalism; disembeddedness; economic aspects; moral economy; neoliberalism

Different Meanings of ‘Knowledge as Commodity’ in the Context of Higher Education - Kauppinen, Ilkka (Critical Sociology (Sage Publications, Ltd.), 2014)
Commodification has been and still is one of the key processes within capitalist market economies. Since the 1970s, different forms of knowledge have increasingly been subjected to this process. In this paper the commodification of knowledge in the field of higher education is defined in a broad sense as an example of the intensive enlargement of capitalism. I argue that knowledge shares some features of public goods and can be subjected to commodification both as an educational product and academic research itself. However, the simple dichotomy of public vs. private good is not nuanced enough to understand the status of knowledge within higher education. How to reconstruct this dichotomy, whether knowledge should be commodified, and how to justify one’s normative stance in this respect are three important issues for further study.
Keywords: academic capitalism; capitalism; capitalists & financiers; commodification; commodification of knowledge; commodity; higher education; knowledge; public goods

Urban poverty and regulation, new spaces and old: Japan and the US in comparison - Mahito Hayashi (Environment & Planning A, 2014)
After the 1970s the new urban poverty (NUP) ballooned in Japan and the US, and it evoked policy responses that produced new, rescaled regulatory spaces to contain the poor on the fringe of social rights and the capital circuit. The paper illuminates this process through the comparison of Japanese and US trajectories, both of which, evolving through economic crises, have established unique pathways. The author first constructs a theoretical framework based on Marxian, Polanyian, and Lefebvrean traditions. Then, he compares national-scale poverty regulation in Japan and the US from the 1950s through the 2000s. Lastly, the author examines how the countries' regulation of a major aspect of the NUP--homelessness--intensified multiscalar reseating processes. The paper concludes that regulation of the NUP represents a significant instance of uneven spatial development of capitalism mediated by the state that requires synthetic research.
Keywords: Japan; United States; capitalism; comparative studies; economic development; financial crises; financial crisis; ghettoization; homelessness; rescaling; the capital circuit; the new urban poverty; the regulation approach; uneven spatial development; urban poor

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange

The Return of Karl Polanyi - Somers, Margaret; Block, Fred (Dissent, 2014)
In the first half century of Dissent’s history, Karl Polanyi almost never made an appearance in the magazine’s pages. On one level this is surprising, because Polanyi was a presence in socialist circles in New York City from 1947 through the mid-1950s, the period of Dissent’s gestation. On another level it is unsurprising, in that Polanyi was a heterodox thinker—even among fellow socialists. With some significant exceptions, it has taken decades to recognize the extraordinary theoretical contributions to socialist thought that he made in his masterpiece, The Great Transformation: The Social and Political Origins of Our Time,first published in 1944.
Keywords: Vienna (Austria); democracy; economics; primacy of politics; socialism

Feminist Reflections on the Scope of Labour Law: Domestic Work, Social Reproduction, and Jurisdiction - Fudge, Judy (Feminist Legal Studies, 2014)
Drawing on feminist labour law and political economy literature, I argue that it is crucial to interrogate the personal and territorial scope of labour. After discussing the “commodification” of care, global care chains, and body work, I claim that the territorial scope of labour law must be expanded beyond that nation state to include transnational processes. I use the idea of social reproduction both to illustrate and to examine some of the recurring regulatory dilemmas that plague labour markets. I argue that unpaid care and domestic work performed in the household, typically by women, troubles the personal scope of labour law. I use the example of this specific type of personal service relation to illustrate my claim that the jurisdiction of labour law is historical and contingent, rather than conceptual and universal. I conclude by identifying some of the implications of redrawing the territorial and personal scope of labour law in light of feminist understandings of social reproduction.
Keywords: decommodification; feminist theory; fictitious commodities; labour law; triple movement

Acerca del renovado interés por Karl Polanyi - Subirats, Joan (Sobre o interesse renovado de Karl Polanyi., 2014)
¿Cómo es posible que un libro escrito hace setenta años despierte hoy un renovado interés y que sirva para hacer mejores diagnósticos sobre la crisis económica y sus posibles alternativas? En este texto trataremos de dar respuesta a este interrogante, mostrando los elementos que hacen de la obra de Polanyi un buen punto de partida para observar la crisis de legitimidad política y los problemas de relación entre economía de mercado y sistema político. La crítica de Polanyi a la naturalización de la economía de mercado es hoy plenamente actual. (Spanish)
Keywords: bens comuns; bienes comunes; capitalismo; crises econômica; crisis económica; economia de mercado; economía de mercado; relaciones estado y sociedad; relações de estado e sociedade

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire

Sociology as a vocation: Moral commitment and scientific imagination - Burawoy, Michael (Current Sociology, 2014)
Public sociology and the sacrifices it entails, richly described in the case studies in this monograph, are driven by moral commitment. This is one element of sociology as a vocation. The other element is sociology as a science. The case studies are built on an embryonic sociology of commodification, understood in its historical dimensions and its global consequences. This sociology of commodification examines the disasters created by third-wave marketization and the bleak future for human existence, thereby, fueling the original moral commitment of public sociology.
Keywords: countermovement; double movement; fictitious commodities; marketization; public sociology

Marketisation, public services and the city: the potential for Polanyian counter movements - Warner, Mildred E.; Clifton, Judith (Cambridge Journal of Regions, Economy and Society, 2014)
Marketisation of urban service delivery gained renewed intensity in the crisis. Mobilising Polanyi’s concept of double movement, we analyse how marketisation of public services both creates and constrains the potential for urban counter movements in the USA and Europe. We identify three main urban responses: ‘hollowing out’, where cities engage in service cut backs; ‘riding the wave’, where cities attempt to harness the market; and ‘push backs’, where cities and citizen movements oppose marketisation. Although the city is constrained by marketisation at national and international levels, we find evidence of push back and, in it, the potential for public service alternatives.
Keywords: city; crisis; double movement; marketisation; public services; urban studies

Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA, Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU, Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Innis and Polanyi: The Search for the Substantive Economy - Rotstein, Abraham (Journal of Economic Issues; Abingdon, 2014)
Economics and the economy have an uneasy relationship. Economics is akin to the logic of mathematics in contrast to the term "economy," which is an institutional framework to provide for material wants. While they overlap in the modern market economy, economics provides distorted results when applied to tribal societies, the economies of antiquity, or modern state-organized economies. Harold A. Innis and Karl Polanyi both attempted to find a different conceptual framework for a truly general economic history. [PUBLICATION ABSTRACT]
Keywords: INNIS, Harold; business & economics - economic systems and theories; economic history; substantiveness; supply and demand

Neo-pluralist political science, economic sociology and the conceptual foundations of the comparative capitalisms literatures - Bruff, Ian; Hartmann, Eva (Capital & Class, 2014)
In this paper, we critically assess two of the key conceptual foundations for the comparative capitalisms (CC) literatures, neo-pluralist political science and economic sociology, in order to identify more clearly the deep intellectual roots of these literatures. Principally, we focus on how the strengths of neo-pluralism and economic sociology – their attention to detail in considering the huge range of ‘types’ of capitalism that exist across the world – come at a high price. Put briefly, the redefinition of ‘capitalism’ as ‘the economy’ concentrates research agendas on the specific political and social conditions found across the world, leaving ‘the economy’ relatively untouched. In consequence, ‘capitalist diversity’ is quickly, and often silently, equated to ‘political diversity’ or ‘social diversity’. As such, a key weakness of CC scholarship, identified by various authors in this Capital & Class special issue – that it does not provide a satisfactory theoretical understanding of capitalist societies – is a problem that runs deeper than the limitations that can be observed in contemporary debates. The implications of our argument are discussed in the conclusion.
Keywords: capitalism; capitalist diversity; comparative capitalisms; economic sociology; neo-pluralism; political economy

The Debate on Globalization and International Revitalization of Labor. A Critical Review - Fleming, Daniel; Søborg, Henrik (Nordic Journal of Working Life Studies, 2014)
This article discusses some alternative or critical theoretical contributions regarding globalization and labor. The main question in this discussion is if there are changes in direction of a possible revitalization of labor movements and if international solidarity can increase due to globalization. This question also relates to discussions of changes in division of work, the concept of work, working class, commodification, decommodification, and new centers of global production--all related to different paradigms or new concepts. The reason or need for reconceptualizing comes from the great transformation of capitalism in forms of neoliberal globalization, in a different direction than predicted by Polanyi. That is, instead of increased public sector decommodification (not profit- or market-oriented production) and national regulation, embedding capitalist markets, as seen after 1945, the last three decades have witnessed a countertransformation and large-scale recommodification by privatizing, disembedding, and deregulating global markets. As a consequence, inequality in income and working life conditions has increased in most countries and been used to press trade unions. Western industrial unions have been declining as many industries and labor-intensive, low-paid jobs moved to developing countries. Most blue-collar jobs are now in Asia, especially China, with about one-third of its employment blue collars. Is the center of global capital-labor contradictions and dynamics moving to the South, with a possibility of a new revitalization of labor and international solidarity? We discuss different optimistic and pessimistic views on a possible international revitalization of labor.
Keywords: commodification; decommodification; globalization; income distribution; international solidarity; knowledge workers; labor organizing; labour organizing; occupational citizenship; precariat; revitalization of labor; skill capture; work environment; working class; working class concept

Radical, reformist, and garden-variety neoliberal: coming to terms with urban agriculture's contradictions - McClintock, Nathan (Local Environment, 2014)
For many activists and scholars, urban agriculture in the Global North has become synonymous with sustainable food systems, standing in opposition to the dominant industrial agri-food system. At the same time, critical social scientists increasingly argue that urban agriculture programmes, by filling the void left by the “rolling back” of the social safety net, underwrite neoliberalisation. I argue that such contradictions are central to urban agriculture. Drawing on existing literature and fieldwork in Oakland, CA, I explain how urban agriculture arises from a protective counter-movement, while at the same time entrenching the neoliberal organisation of contemporary urban political economies through its entanglement with multiple processes of neoliberalisation. By focusing on one function or the other, however, rather than understanding such contradictions as internal and inherent, we risk undermining urban agriculture's transformative potential. Coming to terms with its internal contradictions can help activists, policy-makers and practitioners better position urban agriculture within coordinated efforts for structural change, one of many means to an end rather than an end unto itself.
Keywords: United States; agricultural sociology; alternative food networks; community gardens; food production; food security; neoliberalism; urban agriculture; urban farming; urban studies

Group learning as relational economic activity - Saito, Eisuke; Atencio, Matthew (Educational Review, 2014)
The purpose of this paper is to discuss group learning in line with economic perspectives of embeddedness and integration emanating from the work of Karl Polanyi. Polanyi’s work defines economy as a necessary interaction among human beings for survival; the economy is considered inextricably linked from broader society and social relations rather than autonomous and driven by self-interest in free market conditions. He specifically outlines three key forms of integration that are crucial to economic stability, involving the notions of reciprocity, redistribution, and exchange. These patterns of integration are described as key elements that co-mingle within and structure contemporary group learning within classrooms.
Keywords: collaborative learning; cooperative learning; economic activity; education; embeddedness; embeddedness (socioeconomic theory); group learning; group work in education; reciprocity (commerce); social integration

Género y cuidados: respuestas sociales e institucionales al surgimiento de la sociedad de mercado en el contexto europeo - Carbonell Esteller, Montserrat; Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (GENDER AND CARE: SOCIAL AND INSTITUTIONAL ANSWERS TO THE DEVELOPMENT OF THE MARKET ECONOMY IN EUROPE., 2014)
This article examines from a care approach the social and institutional responses to the development of the market economy in the European context. Studying this long period -which Polanyi called the double movement- is relevant because it constitutes the historical process by which the interests of the market, the logic of profits and its social and scientific naturalization come to dominate. Since then, the importance of care work in people's life, the reproduction of the labour force, and the provision of welfare and social insurance have been ignored. Until very recently, historical analyses have focused on the emergence of the Welfare State, regardless of how the state's answers interacted or modeled with other spheres of welfare provision, especially the family through women's unpaid work. The article focuses on the European experience and the period analyzed comprehends the disintegration of communal and assistance care with the Old Regime Crisis, the development of charity and associations as solutions to the inhibition of the Liberal State in the 19th century -solutions that were limited and insufficient, leading to the state assumption of the care and assistance functions, embryo of the development of later Welfare States after World War II. (English)
Keywords: capitalismo liberal; care; cuidados; estados del bienestar; gender; género; liberal capitalism; modelos asistenciales pre-industriales; pre-industrial mutual aid regimes; welfare state

Actualidad de la crítica de Karl Polanyi a la sociedad de mercados - Maya Ambía, Carlos Javier (Política y Cultura, 2014)
Karl Polanyi's critique of market society is a very powerful tool for understanding our current social reality. It helps us to formulate a creative and purposeful proposal that contributes to build a just, equitable, and more humane society, that would be committed to the future life on the planet. A comparison between the society criticized by Polanyi and ours, leads us to discover the validity of his basic concepts and his method for the preparation of a new critical discourse that not only takes advantage of the legacy of the author, but also expands, clarifies and updates it. (English)
Keywords: crítica social; doble movimiento; double movement; market society; mercado autorregulado; self-regulated market; social critique; sociedad de mercado

Bez zmian na „zielonej wyspie”? Kryzys ekonomiczny w polskich badaniach socjologicznych - Mrozowicki, Adam (Whither Green Island? The Global Economic crisis in Polish sociological research., 2014)
The article presents selected aspects of the discussion about the conditions and consequences of global economic crisis in Polish sociology. The author argues that the relatively limited debate on the nature of the current crisis can be explained by two factors. Firstly, it is the consequence of the dominance of modernisation paradigm in the analysis of the Polish social transformation as well as the marginalisation of two sociologies: critical labour sociology and economic sociology. Secondly, drawing on research carried out by the author on working- class life strategies in the 2000s, the limited debate is the outcome of social "normalisation" and "adaptation" to crisis experiences in the Polish society. Despite the symptoms of collective "demobilisation" in the face of successive crises, adaptation to crises has its social limits. The discourse of global economic crisis contributes to new forms of collective mobilisation in the sphere of work and politics regardless of the dominance of individualistic coping strategies inherited from the first decades of transformation. The "counter-movement" taking place in Poland is expressed in trade union radicalisation and mobilisation of radical-nationalist movements. Both processes are interpreted by the author with the reference to Karl Polanyi's work as the manifestations of self-defence of the society against the expansion of socially uncontrolled market mechanisms.
Keywords: economic crisis; neoliberalism; sociology; the myth of the market

Three Shades of Embeddedness, State Capitalism as the Informal Economy, Emic Notions of the Anti-Market, and Counterfeit Garments in the Mauritian Export Processing Zone - Neveling, Patrick (Research in Economic Anthropology, 2014)
Purpose -- This paper furthers the analysis of patterns regulating capi-talist accumulation based on a historical anthropology of economic activ-ities revolving around and within the Mauritian Export Processing Zone (EPZ). Design/methodology/approach -- This paper uses fieldwork in Mauritius to interrogate and critique two important concepts in contemporary social theory -- "embeddedness" and "the informal economy." These are viewed in the wider frame of social anthropology's engagement with (neoliberal) capitalism. Findings -- A process-oriented revision of Polanyi's work on embedded-ness and the "double movement" is proposed to help us situate EPZs within ongoing power struggles found throughout the history of capital-ism. This helps us to challenge the notion of economic informality as supplied by Hart and others. Social implications -- Scholars and policymakers have tended to see eco-nomic informality as a force from below, able to disrupt the legal-rational nature of capitalism as practiced from on high. Similarly, there is a view that a precapitalist embeddedness, a "human economy," has many good things to offer. However, this paper shows that the practices of the state and multinational capitalism, in EPZs and elsewhere, exactly match the practices that are envisioned as the cure to the pitfalls of capitalism. Value of the paper -- Setting aside the formal-informal distinction in favor of a process-oriented analysis of embeddedness allows us better to understand the shifting struggles among the state, capital, and labor.
Keywords: Mauritius; capitalism; economic anthropology; embeddedness; embeddedness (socioeconomic theory); ethnohistory; export processing zones; informal sector (economics); neoliberalism

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Keywords: Great Transformation, The (Book); primitive societies

The Polanyian Perspective Meets the Varieties of Capitalism: Inspecting the Consequences of the Institutional Changes in South Korea since 1997 - Šitera, Daniel (Perspectives: Central European Review of International Affairs, 2014)
This article attempts to combine the Polanyian perspective on the issue of market societies with an the analysis of the institutional foundations of capitalism that is facilitated by the Varieties of Capitalism(VoC) approach. The article departs fromthe argument that the VoC school has upgraded our insight into the institutional working ofmodern capitalism, but became entrapped in an overt structuralismwhich considers institutional change as just an interplaywithin a self-odering institutional structure.However, the article employs Karl Polanyi's doublemovement, the dialectic of marketizing dis-embedding and socializing re-embedding, to demonstrate that the institutional changemust be rather conceived as embedded in a social life. Only then can one recognize considers that such a change is primarily conditioned by social contests among sentient agents which engage in an ideational struggle over its final outcome. These theoretical reconsiderations are tested on the empirical terrain of Korean capitalism after the Asian Crisis of 1997 and the Global Crisis of 2007. First, the double movement is used to demonstrate that the post-crises institutional changes have transformed Korean capitalism's institutional and societal model from developmentalism to embedded neoliberalism. Second, it is documented that this transformation has been characteristic of certain ideational struggles which turned into a socially contested, largely contradictory, uneven, and open-ended process.
Keywords: Asia; POLANYI, Karl, 1886-1964; South Korea; capitalism; developmentalism (economics); double movement; financial crises; global financial crisis, 2008-2009; international affairs; neoliberalism; varieties of capitalism

Crisis del modelo neoliberal, hacia una planificación regional. Un aporte polanyiano - Valderrama Saud, Paula (Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution., 2014)
Using Karl Polanyi's analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called "mass democracy." Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the beginning of a new era characterized by greater regional planning and a plurality of development paths. (English)
Keywords: European Union; Latin America; crisis; democracia; democracy; globalization; government policy; market; mercado; neoliberalism; neoliberalismo; planificación regional; regional planning

Embedding Trade Liberalisation in Social Policy: A Research Agenda on Social Regionalism and the Global South [article] - Ashiagbor, Diamond (Northern Ireland Legal Quarterly, 2014)
Underpinning this article is the proposition that regional integration with a social dimension has the potential to engender a more equitable pattern of globalisation. The empirical focus of the article is on the ex)tent to which the insights of 'embedded liberalism' associated with regional economic integration between he industrialised nations of the European Union (EU)can be applied to regional economic integration within sub-SaharanAfrica. The article contends that EU market liberalisation has been embedded within labour market institutions and institutions of social citizenship at the domestic level. These have served as social stabilisers to counter the far-reaching effects of the internal market and global trade. Less industrialised nations have never enjoyed adjustment mechanisms of this sort, raising the question for this article, and for further research: in which legal and institutional structures can these nascent forms of market integration at regional and sub-regional level be embedded? In examining the interaction between trade liberalisation and labour standards, I draw on the work of Karl Polanyi. Central to his key work, The GreatTransformation,is the assertion that all economies are enmeshed in non-economic institutions, although the forms and depth of this social embedding may differ. Drawing on Polanyi, I argue that laissez-faire economic liberalism may be offset by principles of social protection at national and, in some instances, regional level - a 'counter-movement' to the economic insecurity arising from globalisation.
Keywords: United Kingdom; social regionism; trade liberalisation

The Pyrrhic Triumph of Finance Capital and the Return of Polanyi - Harrison, Trevor W. (Athens Journal of Social Sciences, 2014)
This paper examines the declining support for centrist parties in many western countries. Using the seminal ideas of Karl Polanyi, the paper argues this decline is attributable to the rise of neo-liberal free market policies that have resulted in widespread insecurity and led many voters to seek out political alternatives on the right and left. The paper further examines possible reasons why parties of the right, rather than the left, have been more successful at this historical juncture in channeling political disenchantment.
Keywords: countermovement; fascism; finance capital; neoliberalism

From the Apocalypse to the Revolution - Pellicani, Luciano (Telos, 2014)
The article discusses the emergence of millennialism, which is considered as one of the outcomes of the spiritual victory of Christianity over the Greco-Roman culture. The formulation of the historical-sociological category of cultural catastrophe by Hungarian economic historian Karl Polanyi is tackled. The presence of a divine messenger as one of the three elements of a messianic movement is cited. The concepts of revolutionarism, Jacobinism and Marxism are also addressed.
Keywords: Christianity; POLANYI, Karl, 1886-1964; communism; critical theory; cultural catastrophe; messianism; millennialism

Kari Polanyi: Nine Decades of Scientific and Militant Life - Rioux, Michele (Revue interventions economiques/Papers in Political Economy, 2014)
Keywords: biography; history of economic thought: individuals

The Renewal of a Critical Theory of Capitalism and Crisis – A Comment on Nancy Fraser’s Interpretation of Polanyi’s works - Deutsche Digitale Bibliothek - Sparsam,, J.; Eversberg, D.; Haubner, T.; Mader, D.; Muraca, B.; Hanno, P. (Working Paper 7/2014 of the DFG-Kollegforscher_innengruppe Postwachstumsgesellschfaten., 2014)
The paper examines Nancy Fraser’s Polanyian reading of the current capitalist crisis and her expansion of Polanyi’s notion of the ‘double movement’–social forces struggling for marketization and social protection– into a ‘triple movement’ by adding the struggle for emancipation as a third factor. In its first part, the paper reviews Fraser’s central arguments with a special focus on her reading of Polanyi’s idea of the “fictitious commodities” land, labor, and money. Second, the authors examine Fraser’s conceptualization of social forces, domination and emancipation drawing on Environmental Philosophy, Political Ecology, Marxism, Feminism, Social Philosophy as well as Polanyi himself. In the end, the paper argues that Fraser’s conception of capitalism and emancipation are in need of improvement if critical theory wants to adequately grasp the current crisis of capitalism.
Keywords: FRASER, Nancy; fictitious commodities; interpretation; triple movement

Reflections on the civil war in the period of the ideologies (1929-1939). Carl Schmitt and Karl Polanyi - Visone, Tommaso (Giornale di Storia Costituzionale, 2014)
The aim of this paper is to discuss the concept of civil war during the Thirties (1929-1939). To this purpose, the work analyses the development of the Civil War discourse in the thought of Carl Schmitt and Karl Polanyi, trying to focalize on the relationship between its consequences on the civil war and the conflicting ideologies which characterised that period. Hence, the Civil war is described, through these different narrations, showing two different sides of modernity: the destructive and dangerous one on the one hand, and the transformative and soteriological on the other.
Keywords: 1930s; SCHMITT, Carl; civil war; ideology